Student Perceptions of the Impact of “Quality Matters” Certified Online Courses on their Learning and Engagement - Ayesha Sadaf; Florence Martin; Lynn Ahlgrim-Delzell (Online Learning, 2019)
The Quality Matters (QM) is one of the most widely-adopted set of standards for best practices in online courses to promote student learning. In this study, we examined student perceptions of the impact of QM certified courses on students learning and engagement. Fifty graduate students enrolled in online courses completed a survey developed based on the QM rubric items. The QM framework includes 43 standards in eight categories. Among eight categories, Course Activities and Learner Interactionwere rated to have the highest impact and Learning Objectiveswere rated to have the second highest impact on both student learning and engagement. The exploratory factor analysis revealed that 12 factors explained 88.89% of the variance of the impact on learning and 8 factors explained 85.72% of the variance of the impact on engagement. Clear expectations loaded as the highest factor for both learning and engagement.